1968
DOI: 10.1161/01.res.23.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intrarenal Hydrostatic Pressure and Hemodynamically Induced Changes in Sodium Excretion

Abstract: Deep intrarenal venous pressure was used as an index of renal capillary pressure to test the proposal that physically induced changes in sodium reabsorption may be mediated by changes in Starling forces across the capillary. Renal vasodilatation produced natriuresis associated with immediate increases in intrarenal venous pressure. Increased arterial pressure was accompanied by further natriuresis and initially increased intrarenal pressure in vasodilated kidneys. Plasma load was always accompanied by increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

1969
1969
1982
1982

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 14 publications
0
29
1
2
Order By: Relevance
“…The observations of de Wardener, Mills, Clapham, and Hayter (16), that natriuresis during saline infusion can be dissociated from the rate of glomerular filtration and mineralocorticoid activity, have led to investigations attempting to define further these additional natriuretic mechanisms. Recent studies have demonstrated the roles of renal perfusion pressure (11,13,14), renal vascular resistance (11,26) plasma protein concentration (11,26), and plasma sodium concentration (27,28) in the natriuretic response to volume expansion. In the present study we examined the effect of increasing the hematocrit to normal values during sustained volume expansion with either saline or plasma.…”
Section: Resultsmentioning
confidence: 99%
“…The observations of de Wardener, Mills, Clapham, and Hayter (16), that natriuresis during saline infusion can be dissociated from the rate of glomerular filtration and mineralocorticoid activity, have led to investigations attempting to define further these additional natriuretic mechanisms. Recent studies have demonstrated the roles of renal perfusion pressure (11,13,14), renal vascular resistance (11,26) plasma protein concentration (11,26), and plasma sodium concentration (27,28) in the natriuretic response to volume expansion. In the present study we examined the effect of increasing the hematocrit to normal values during sustained volume expansion with either saline or plasma.…”
Section: Resultsmentioning
confidence: 99%
“…These changes in renal hemodynamics occur, at least in part, as a result of a direct action of dopamine on the renal vasculature (36), and, as they may be selectively attenuated by haloperidol and chlorpromazine, they are probably mediated by specific dopamine receptors in the kidney (9,10). Whereas changes in renal vasodilatation may be linked to the increase in sodium excretion by virtue of a decrease in colloid oncotic pressure and an increase in hydrostatic pressure in peritubular capillaries such that the tubular reabsorption of sodium is decreased (37)(38)(39), a direct effect of dopamine on tubular transport of sodium may also occur. The observation of a decrease in the tubular reabsorption of sodium which could not be explained in terms of events in the peritubular capillary has led to postulation of the existence of a natriuretic substance or substances (40).…”
Section: Discussionmentioning
confidence: 99%
“…The available data on the effect of peritubular pressure changes in mammalian kidneys do not lend themselves to comparison. Pressure or flux values were estimated only indirectly (10,12,13), and the effects of only small increments of PPT tested.…”
Section: Discussionmentioning
confidence: 99%